2018
DOI: 10.3390/en11081965
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Olive Mill Solid Wastes Pellets Combustion in a Counter-Current Fixed Bed Reactor

Abstract: Combustion tests and gaseous emissions of olive mill solid wastes pellets (olive pomace (OP), and olive pits (OPi)) were carried out in an updraft counter-current fixed bed reactor. Along the combustion chamber axis and under a constant primary air flow rate, the bed temperatures and the mass loss rate were measured as functions of time. Moreover, the gas mixture components such as O2, organic carbon (Corg), CO, CO2, H2O, H2, SO2, and NOx (NO + NO2) were analyzed and measured. The reaction front positions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…Other authors carried out the combustion of OS pellets in a 40 kW counter-current fixed bed reactor and assessed some combustion parameters. The results achieved with OS pellets were quite similar to those obtained with the standard wood pellets that are used currently in European biomass markets [115].…”
Section: Combustionsupporting
confidence: 77%
“…Other authors carried out the combustion of OS pellets in a 40 kW counter-current fixed bed reactor and assessed some combustion parameters. The results achieved with OS pellets were quite similar to those obtained with the standard wood pellets that are used currently in European biomass markets [115].…”
Section: Combustionsupporting
confidence: 77%
“…Wongsiriamnuay and Tippayawong [15] in their work describe the problem of developing post-production maize waste, proposing the production of fuel pellets from them. The tests carried out on a laboratory bench with a closed chamber show that the produced pellet had favorable physical properties, in other words, a density of more than 1000 kg•m −3 (db) if the compaction temperature was higher than 80 • C. Mami et al [16] found that the gaseous emissions from olive waste pellets are produced in acceptable concentrations compared to Germany and European standards and the quality of pellets obtained in their experiment was similar to standard wood pellets, which are used currently in European markets.…”
Section: Introductionmentioning
confidence: 99%
“…Note that biomass can be valorized energetically by three routes: physicochemical, biochemical and thermochemical [14] routes. The thermochemical route includes pyrolysis [15,16], combustion [17,18], gasification [19,20] etc. In the present study, two different processes were investigated: an isothermic pyrolysis for producing charcoal in a horizontal furnace, and then a gasification of the prepared charcoal in a Macro-TG.…”
Section: Introductionmentioning
confidence: 99%